Margret & H.A. Rey's Curious George says thank you - Meyer, Emily Flaschner; Bartynski, Julie M.; Hines, Anna Grossnickle; Rey, Margret; Rey, H. A. (Hans Augusto), 1898-1977. (Boston : Houghton Mifflin Harcourt, 2012)
When George receives a thank-you card in the mail, he plans to send a card to all the people he wants to thank.
Keywords: Curious George -- (Fictitious character) -- Juvenile fiction; Monkeys -- Juvenile fiction; Thank-you notes -- Juvenile fiction; Fiction